Winter warming effects on soil nitrate leaching under cover crops: A field study using high-frequency weighing lysimeters - Lapierre, Jared; Machado, Pedro Vitor Ferrari; Debruyn, Zachary; Brown, Shannon E.; Jordan, Sean; Berg, Aaron; Biswas, Asim; Henry, Hugh A. L.; Wagner-Riddle, Claudia (Frontiers in Environmental Science, 2022)
Leaching of nitrate (NO3-) – a reactive nitrogen form with impacts on ecosystem health – increases during the non-growing season (NGS) of agricultural soils under cold climates. Cover crops are effective at reducing NGS NO3- leachin, but this benefit may be altered with less snow cover inducing more soil freezing under warmer winters. Our objective was to quantify the effect of winter warming on NO3- leaching from cover crops for a loamy sand (LS) and a silt loam (SIL) soil. This research was conducted over 2 years in Ontario, Canada, using 18 high-precision weighing lysimeters designed to study ecosystem services from agricultural soils. Infra-red heaters were used to simulate warming in lysimeters under a wheat-corn-soybean rotation planted with a cover crop mixture with (+H) and without heating (-H). Nitrate leaching determination used NO3- concentration at 90 cm (discrete sampling) and high temporal resolution drainage volume measurements. Data were analyzed for the fall, overwinter, spring-thaw, post-planting, and total periods (i.e., November 1 to June 30 of 2018/2018 and 2018/2019). Warming significantly affected soil temperature and soil water content – an effect that was similar for both years. As expected, experimental units under +H presented warmer soils at 5 and 10 cm, along with higher soil water content than -H lysimeters, which translated into higher drainage values for +H than –H, especially during the overwinter period. The warming effect on NO3- concentration was not as clear as the results for soil temperature, water content, and drainage. For the overwinter period of 2017/2018, there was a trend for the interaction between soil type and heating regime, whereas in 2018/2019, soil type affected NO3- concentration, with LS > SIL. The drainage and NO3- concentrations exhibited high spatial variation, which likely reduced the sensitivity to detect significant differences. Thus, although absolute differences between LS vs SIL and +H (LS) vs –H (LS) were large, only a trend occurred for the interaction between heating and soil type in 2018/2019. However, our research demonstrates that soil heating can influence NO3- leaching and that cover crops can reduce adverse effects of winter warming.